The fully bio-based bilayered flame retardant treatment for paper via natural bio-materials - Sun, Zhihao; Liu, Xinlong; Hu, Qiaosheng; Zhao, Qing; Qi, Xuyao; Xu, Fei; Li, Jingxian; Ma, Zhongfei (Frontiers in Chemistry, 2024)
In this paper, we report a novel method for enhancing the flame retardancy of wood-based paper by utilizing natural biomaterials. The research constructed a bilayer structure coating on paper fiber surfaces, incorporating mixed starch (MS), adenosine triphosphate (ATP), and phytic acid (PA) as natural bio-based flame retardants. The structural configuration of the coating comprises MS/ATP and MS/PA, which were sequentially assembled as bottom and top parts, respectively, through pneumatic spraying. The surface morphological features and elemental distribution analysis of treated paper indicated that bio-materials were successfully assembled, which resulted in a uniform flame retardant coating on the paper fiber surface. Compared to the untreated paper, the limiting oxygen index of 20 bilayers (BL) treaed paper increased substantially from 19.07% to 24.00%, and the thermogravimetric analysis showed out the residual char yield enhanced from 23.80% to 38.10%. The cone calorimeter test results of 20 BL treated paper have approximately a 50.00% reduction than the untreated paper in both peak and total heat release rates. During thermal exposure, the top and bottom parts of the bilayer structure coating are successively flame retarded prior to paper fiber degrading. The method presented in this paper provides an environmentally sustainable approach for producing flame retardant wood-based paper.